2013
DOI: 10.1055/s-0032-1326725
|View full text |Cite
|
Sign up to set email alerts
|

Opening Wedge Osteotomy for Distal Radius Malunion: Dorsal or Palmar Approach?

Abstract: Background?There are various technical variations to consider when performing a corrective osteotomy of a distal radius malunion. We chose two of the more commonly reported techniques and compared the results of volar (palmar) osteotomy and fixation with dorsal osteotomy and fixation. Method?Within a continuous cohort of patients who had undergone corrective osteotomy for a malunited Colles fracture, two groups could be identified retrospectively. In 8 patients a dorsal approach was used. A structural trapezo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
0
19
0
4
Order By: Relevance
“…The authors came to the concept that the stiff characteristics of fixed angle volar plates could provide an alternative to the traditional techniques of distal radius osteotomy including structural bone grafting and dorsal plate fixation or external fixation. Comparable results in terms of anatomic restoration of the distal radius, ROM improvement in the radiocarpal joint, and restoration of the anatomic relationships of the distal radioulnar join were obtained by Rothenfluh et al [29] , Wada et al [23] , and Peterson et al [28] . All these authors used bone graft from the iliac crest with a comparable DASH scores and no complications.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The authors came to the concept that the stiff characteristics of fixed angle volar plates could provide an alternative to the traditional techniques of distal radius osteotomy including structural bone grafting and dorsal plate fixation or external fixation. Comparable results in terms of anatomic restoration of the distal radius, ROM improvement in the radiocarpal joint, and restoration of the anatomic relationships of the distal radioulnar join were obtained by Rothenfluh et al [29] , Wada et al [23] , and Peterson et al [28] . All these authors used bone graft from the iliac crest with a comparable DASH scores and no complications.…”
Section: Discussionmentioning
confidence: 80%
“…The healing time was comparable using the graft or not (mean 12.5 wk), ranging from 7.5 [24] to 16 [25,26] wk. The mean DASH score improvement was 23 points both in the studies describing the use of the graft (range, 11-46) [22][23][24][27][28][29] , and in those not using the graft (range, 13-28) [25,[30][31][32] . Finally, few studies reported postoperative complications [11,22,23,26,29,32] .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Rothenfluh et al group have compared dorsal and volar approaches for distal radius malunion and cited the benefits of volar approach like low tendon irritation problems and easy learning curve. 14 Jupiter and Ring demonstrated that performing early osteotomy facilitates the surgical procedure (osteotomy by means of immature bone tissue with less soft tissue retraction and less instability of the distal radioulnar joint) and diminishes the time off work. 15,16 For this reason, young patients with dorsal angulation greater than 20 degrees should be considered to be in a precursor situation of the degenerative process (arthrosis) and a surgical procedure should be indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-articular DRF (IDRF), a severe form of DRF, accounts for about 25% of total DRF [3]. Currently, it is still very challenging to completely recover from the IDRF, because it is necessary to achieve not only an anatomical reduction [4,5], i.e., complete reconstruction of radius and the articular surface [6], but also a strong and precise internal fixation to facilitate early rehabilitation [7]; otherwise complications such as traumatic arthritis will often occur, which will seriously affect the function of the hands and wrists [8,9].…”
Section: Introductionmentioning
confidence: 99%